PROCEEDINGS OF INVALIDITY OF TESTAMENT IN AUSTRIAN AND SERBIAN LEGISLATION - Živojinović, Dragica (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
Proceedings of invalidity of effective testament, based on facts presuming incompliance with the previously expressed last will of the testator, as being prescribed in several contemporary legislations, distinct from the revocation of a testament as a strictly personal act by which the testator explicitly or tacitly expresses or manifests animus revocandi. The subject of this paper is the analysis of legal solutions that regulate cases when the last will can be revoked in Austrian law (the cessation of the partnership or kinship relations after making a last will and exclusion of the single child from the will due to the testator's misconception) and in Serbian law (the substantial change of circumstances which, in time of making the will, were decisive motive for the testator to make the bequest of certain content). Having researched the facts as the basis for the presumption of disagreement with the pronounced last will of the testator and considered other conditions as prerequisites for the application of this institute, as well as their comparison, the author concludes that the legislator's intervention into freedom of testation could be justified only in case if such intervention is crucial for its execution. In other cases such intervention bears the risk of imposing additional restrictions, even the interference into testamentary freedom.
Keywords: testament (last will); freedom of testation; proceedings of invalidity of testament; revocation of testament; testator's presumed will